Pengaruh Struktur Modal, Aktivitas, Current Ratio, dan Profitabilitas Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur - Fifi Ester Nofriyani; Ratna Anda Kristal Halawa; Keumala Hayati (Forum Kerjasama Pendidikan Tinggi, 2021)
This study aims to examine the effect of DER, TATO, CR and ROA on PBV partially or simultaneously in manufacturing companies on the Indonesia Stock Exchange in the 2016–2019 period. The research was conducted by using multiple linear regression analysis and testing used the SPSS program. The population of this study was 165 companies and a sample of 49 companies with a total of 196 data. From the research conducted, the results of the partial test revealed that: DER and TATO affect PBV partially which is negative and not significant, and CR affects PBV partially which is negative significant, and ROA affects PBV partially positive and significant. DER, TATO, CR, and ROA simultaneously affect PBV which is significant